2013
DOI: 10.1063/1.4824457
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a hairpin vortex in a shear-thinning fluid governed by a power-law model

Abstract: The effect of a shear-thinning fluid governed by a power-law model on the evolution of a hairpin vortex in a wall-bounded flow was studied by means of direct numerical simulation. With a fixed Reynolds number and hairpin vortex strength, the effect of shear-thinning on vortex evolution could be isolated. The primary observation is that very early in time shear-thinning has the effect of reducing the production of vortex kinetic energy and dramatically increasing viscous dissipation. This leads to a delay in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…with a relatively monotonic influence of the power-law index. 35,36 Another example is the study of a hairpin vortex in a wallbounded flow by Zhen et al, 37 for a Reynolds number range (4000-8000) higher than for the present study. The authors observed that shear-thinning properties decreased the production of vortex kinetic energy, increased the viscous dissipation, and delayed the transition to a turbulent state.…”
Section: Introductionmentioning
confidence: 57%
“…with a relatively monotonic influence of the power-law index. 35,36 Another example is the study of a hairpin vortex in a wallbounded flow by Zhen et al, 37 for a Reynolds number range (4000-8000) higher than for the present study. The authors observed that shear-thinning properties decreased the production of vortex kinetic energy, increased the viscous dissipation, and delayed the transition to a turbulent state.…”
Section: Introductionmentioning
confidence: 57%
“…where μ represents the dynamic viscosity used in equation (4), K is the consistency index, n is the power-law exponent, and S is the strain rate tensor [33].…”
Section: S S Kmentioning
confidence: 99%
“…The dynamic viscosity of the non-Newtonian fluid can be described by the power law model where μ is the dynamic viscosity used in equation (5), K is the consistency coefficient, n is the power-law exponent, and S is the shear strain rate tensor. 34…”
Section: Numerical Techniquementioning
confidence: 99%
“…where is the dynamic viscosity used in equation 5, K is the consistency coefficient, n is the power-law exponent, and S is the shear strain rate tensor. 34…”
Section: Sph Conversation Equationsmentioning
confidence: 99%